Efektifitas Produksi Industri Rumahan Dodol Betawi Di Pondok Aren, Tangerang Selatan - Dewa Guna Negara Putra; Ahmad Riyas; Supela Supela; M. Faqih Budianto; Panji Adyputra; Rizki Nur Fahmi; Yanti Budiasih (Indonesian Journal of Economics Application (IJEA), 2018)
Dodol is including traditional food which is already known in various regions of Indonesia. Dodol is a kind of food made from sugar and brown sugar and mix the ingredients. Maintaining cultural heritage therefore become very important. In line with this, the researches related to this sweet snack becomes very important. This article presents the results of research on the effectiveness of the production the dodol managed by a home industry in South Tangerang. The results of the data analysis are elaborated any further in this article.